Mechanical Resonators: Single‐Layer MoS2 Mechanical Resonators (Adv. Mater. 46/2013). (December 2013) - Castellanos‐Gomez, Andres; van Leeuwen, Ronald; Buscema, Michele; van der Zant, Herre S. J.; Steele, Gary A.; Venstra, Warner J.
<x xml:space="preserve">Abstract</x> Single‐layer molybdenum disulfide (MoS2) mechanical resonators are fabricated by Andres Castellanos‐Gomez and co‐workers on page 6719. The dynamics of these atomically thin resonators are studied by optical interferometry: they behave as membranes with resonance frequencies in the range of 10 to 30 MHz and quality factors up to 109. Clear signatures of non‐linear resonance in these atomically thin resonators are also shown. Due to the combination of excellent mechanical properties with an intrinsic large direct bandgap, single‐layer MoS2 mechanical resonators have a great potential for application as nano‐electromechanical systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>